2022
DOI: 10.1136/bmjopen-2021-059583
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of reproductive tract infections including sexually transmitted infections among married women in urban and peri-urban mid to low socioeconomic neighbourhoods of Delhi, North India: an observational study protocol

Abstract: IntroductionThe Global Health Sector Strategy on sexually transmitted infections (STIs), endorsed by the World Health Assembly in 2016 aims to end STIs as public health threat by 2030. WHO conducts global estimates of prevalence to monitor progress towards achieving the same. However, limited laboratory confirmed data exist of STIs and reproductive tract infections (RTIs) apart from few prevalence surveys among key populations and clinic-based reports, including in India. Syndromic approach is the cornerstone … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 17 publications
1
1
0
Order By: Relevance
“…In Figure 3, statistical analysis showed that in a positive culture the incidence of infection in the age group < 30 years was significantly higher compared to other age groups at p < 0.008. Similar results (Dhabhai et al, 2022) from India showed the highest prevalence of infection in ages > 30 years. The findings of this study agreed with those of Lamichhane et al (2014) from Nepal, who found the highest prevalence of infection in the age group 20-29 years.…”
Section: Isolation and Identificationsupporting
confidence: 82%
“…In Figure 3, statistical analysis showed that in a positive culture the incidence of infection in the age group < 30 years was significantly higher compared to other age groups at p < 0.008. Similar results (Dhabhai et al, 2022) from India showed the highest prevalence of infection in ages > 30 years. The findings of this study agreed with those of Lamichhane et al (2014) from Nepal, who found the highest prevalence of infection in the age group 20-29 years.…”
Section: Isolation and Identificationsupporting
confidence: 82%
“…The Global Health Sector Strategy on sexually transmitted infections (STIs), was endorsed by the World Health Assembly in 2016 to end STIs as a public health threat by 2030. WHO conducts global prevalence surveys to monitor progress towards achieving this goal [15].…”
Section: Discussionmentioning
confidence: 99%